Strigolactones and Auxin Cooperate to Regulate Maize Root Development and Response to Nitrate. (28th January 2021) - Ravazzolo, Laura; Boutet-Mercey, Stéphanie; Perreau, François; Forestan, Cristian; Varotto, Serena; Ruperti, Benedetto; Quaggiotti, Silvia
Abstract: In maize, nitrate regulates root development thanks to the coordinated action of many players. In this study, the involvement of strigolactones (SLs) and auxin as putative components of the nitrate regulation of lateral root (LR) was investigated. To this aim, the endogenous SL content of maize root in response to nitrate was assessed by liquid chromatography with tandem mass Spectrometry (LC–MS/MS) and measurements of LR density in the presence of analogues or inhibitors of auxin and SLs were performed. Furthermore, an untargeted RNA-sequencing (RNA-seq)-based approach was used to better characterize the participation of auxin and SLs to the transcriptional signature of maize root response to nitrate. Our results suggested that N deprivation induces zealactone and carlactonoic acid biosynthesis in root, to a higher extent if compared to P-deprived roots. Moreover, data on LR density led to hypothesize that the induction of LR development early occurring upon nitrate supply involves the inhibition of SL biosynthesis, but that the downstream target of SL shutdown, besides auxin, also includes additional unknown players. Furthermore, RNA-seq results provided a set of putative markers for the auxin- or SL-dependent action of nitrate, meanwhile also allowing to identify novel components of the molecular regulation of maize root response to nitrate. Globally, the existence of at least four different pathways was hypothesized: one dependent on auxin, a second one mediated by SLs, a third deriving from the SL-auxin interplay, and a last one attributable to nitrate itself through further downstream signals. Further work will be necessary to better assess the reliability of the model proposed.